2011
DOI: 10.1534/genetics.110.125062
|View full text |Cite
|
Sign up to set email alerts
|

A Map-Based Cloning Strategy Employing a Residual Heterozygous Line Reveals that the GIGANTEA Gene Is Involved in Soybean Maturity and Flowering

Abstract: Flowering is indicative of the transition from vegetative to reproductive phase, a critical event in the life cycle of plants. In soybean (Glycine max), a flowering quantitative trait locus, FT2, corresponding to the maturity locus E2, was detected in recombinant inbred lines (RILs) derived from the varieties “Misuzudaizu” (ft2/ft2; JP28856) and “Moshidou Gong 503” (FT2/FT2; JP27603). A map-based cloning strategy using the progeny of a residual heterozygous line (RHL) from the RIL was employed to isolate the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
413
4
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(453 citation statements)
references
References 91 publications
23
413
4
13
Order By: Relevance
“…5), suggesting that one or more factors other than E1 is (are) involved in the control of FT2a expression. Watanabe et al (2011) found that the E2 gene (a soybean ortholog of GI) mainly controls flowering time through the regulation of FT2a, not FT5a. Different expression profiles of FT2a and FT5a indicate that, in addition to the PHYA-mediated E1 pathway, another mechanism may control the two FT genes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5), suggesting that one or more factors other than E1 is (are) involved in the control of FT2a expression. Watanabe et al (2011) found that the E2 gene (a soybean ortholog of GI) mainly controls flowering time through the regulation of FT2a, not FT5a. Different expression profiles of FT2a and FT5a indicate that, in addition to the PHYA-mediated E1 pathway, another mechanism may control the two FT genes .…”
Section: Discussionmentioning
confidence: 99%
“…The three loci (E1, E3, and E4), together with E2, an ortholog of Arabidopsis GIGANTEA (GI; Watanabe et al, 2011), are major contributors to the variation in flowering time among soybean cultivars (Xu et al, 2013;Tsubokura et al, 2014). Photoperiod insensitivity in cultivars adapted to high-latitude environments has been independently and repeatedly generated through mutations at E1, E3, and E4 (Tsubokura et al, 2013;Xu et al, 2013).…”
mentioning
confidence: 99%
“…Homologues of GI and FKF1 have been reported in a wide variety of vascular plants from lycophytes to angiosperms 8 . The function of GI in the regulation of photoperiodic flowering has been shown to be common across several angiosperm species [9][10][11][12][13] . However, neither GI nor FKF1 orthologues have yet been identified in fully sequenced non-vascular plants, including the moss Physcomitrella patens 8 .…”
mentioning
confidence: 99%
“…Glyma08g47810 (Kim et al, 2012;Kong et al, 2010;Zhai et al, 2014) GIGANTEA (GI) AT1G22770 (Fowler et al, 1999) Glyma09g07240 (Jung et al, 2012) Glyma10g36600 (Kim et al, 2012;Watanabe et al, 2011) LEAFY ( Matsuzaki, H., Dong, S., Loi, H., Di, X., Liu, G., Hubbell, E., Law, J., Berntsen, T., Chadha, M., Hui, H., et al (2004). Genotyping over 100,000 SNPs on a pair of oligonucleotide arrays.…”
Section: Aim and Objectives Of Researchmentioning
confidence: 99%
“…In legumes such as Pisum sativum (pea), Glycine max (Soybean) and Medicago truncatula (Medicago), studies on flowering gene orthologues have discovered several genes with a conserved role in the regulation of flowering time in response to photoperiod. However, the function of these CO homologues in photoperiod response is still not clear (Hecht et al, 2005;Hecht et al, 2007;Jiang et al, 2011;Liu et al, 2011;Watanabe et al, 2011;Weller et al, 2012;Wong et al, 2014).…”
Section: Timing Of Cab Expression (Cct)mentioning
confidence: 99%